Purposeful building of social capital and the adoption of essential tools and technologies in impoverished communities in the Philippines - LIM, Chon Phung (Institutional Knowledge at Singapore Management University, 2018)
Despite its popularity and a wide range of applications, social capital is a contested concept. There is also no agreement on whether social capital responds well to external interventions. Many scholars found no or, at most, mixed impacts that social capital can be purposefully developed. However, Burt and Ranchi (2007) and Janicik and Larrick (2005) provided compelling evidence that simple network training can significantly improve participants’ ability to see gaps in their network and develop social capital. The manifestations of social capital are context-dependent and complex, and rarely map into a single discipline or methodology (Jones and Woolcock, 2007). Hence, an exploratory sequential mixed-method study was adopted (Creswell and Plano Clark, 2011). Six remote communities (barangays) from three municipalities in Northern Samar in the Philippines were selected as case-study sites for this research. My journey to Northern Samar, one of the most impoverished regions in the Philippines, started from my firm belief that developing the social networks and capital of the community leaders of these impoverished communities can be a viable intervention to improve their livelihoods. The research builds on two theoretical foundations. First, findings in cognitive social networks that individuals’ perception of their network can improve their ‘ability to harness the social capital embedded in the network’ and influence their ‘decisions and behaviour’ (Janicik and Larrick, 2005; Brands, 2013). Second, Burt’s (1992) ‘structure holes’ theory or missing connections between people inhibit information flow, and the advantage of being network brokers to exploit opportunities from separate and non-redundant information in their networks (Burt 2000, 2005, 2009). The goals of my research are, first, to demonstrate that community leaders, regardless of their socio-economic background, respond well to simple intervention to purposefully develop their social networks and capital within a short period of three to six months. Second, the purposefully developed social capital will lead to impactful actions that can help them gain better access to productivity-enhancing resources to improve yields and incomes. Third, an alternative policy recommendation on how farmers and fishermen can gain better access to affordable financial resources is recommended. Finally, to develop a practical and holistic approach to assess and implement future social impact initiatives in impoverished communities.